The Museum and the Killing Jar: How Animal Crossing’s Insects Reveal Videogames’ Object Afterlife - Bailey, Andrew Remington (Loading)

(untitled) (Canadian Game Studies Association, 2020)
Within the Animal Crossing series, players have always had the ability to collect insects and then donate them to a museum where they can then be permanently exhibited. This paper makes the argument that this collecting and exhibiting of game objects works to reflect many of the ways that videogames have begun to take up an increasingly prominent place within real world  institutional exhibitions, archives, and collections. Through a conjoined lens that is equally informed by games preservation, etymology, and art history this essay works to unpack the intricacies of how the museum and collecting function with the Animal Crossing series. This examination of Animal Crossing will then be applied more broadly to two museums (the MoMA and the V&A) exhibition case studies, making the comparative argument that overtly taxonomic methods of display and archiving can work to deaden videogames’ inherently mutable vitality. By speculatively thinking of videogames as things akin to the bugs of Animal Crossing, to be kept alive throughout the archival process rather than dead objects to be preserved, a new, more productive lens of videogame curation can be gleaned.